1998
DOI: 10.1542/peds.101.2.e2
|View full text |Cite
|
Sign up to set email alerts
|

Does Culture Confirmation of High-sensitivity Rapid Streptococcal Tests Make Sense? A Medical Decision Analysis

Abstract: ABSTRACT. Objective. Since the 1990 publication of a decision analysis, in which the treatment of pharyngitis in children was evaluated, a number of assumptions important in that analysis have changed. Updating many of the assumptions and costs used in that analysis to reflect the conditions currently found in a large, suburban pediatric practice, a cost-effectiveness analysis was performed in which four strategies for the treatment of pharyngitis were considered: treat all, high-sensitivity antigen test, cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
12

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 32 publications
1
41
0
12
Order By: Relevance
“…There have been modelling studies in children 60 and adults, 61 but these studies did not collect resource use or quality of life data, and the studies came to opposite conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…There have been modelling studies in children 60 and adults, 61 but these studies did not collect resource use or quality of life data, and the studies came to opposite conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…16 On the other hand, culture confirmation of negative high-sensitivity rapid antigen tests is not cost-effective. 17 Other limiting factors for throat cultures are its logistics. Providing patient follow-up and prescribing or discontinuing treatment are cumbersome, particularly in the ED setting.…”
mentioning
confidence: 99%
“…Furthermore, despite the probable beneficial effect of tonsillectomy, it is still a surgical procedure with an associated morbidity that includes possible hospitalization, risks of anesthesia, prolonged throat pain, and financial costs. Several surgical related complications including; throat pain, postoperative nausea and vomiting, delayed feeding, voice changes, hemorrhage, and rarely death have been reported and must be considered [54,55] Although this strategy of prophylactic treatment of all patients with recurrent pharyngitis might be debated to expose patients to unnecessary side effects and increased antibiotics resistance [56,57], however several studies have found this to be the most cost-effective strategy with the greatest reduction for potential complications and death [58][59][60]. It has been reported that the health benefits gained from reducing complications and socioeconomic burden much outweighs the minimal risk of antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%